2023
DOI: 10.1002/cssc.202201921
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Phase Synergies with Doping Engineering Over Ni Electrocatalyst Featuring Regulated Electronic State for Accelerated Urea Oxidation

Abstract: Exploring high‐performing Ni‐based electrocatalysts for the urea oxidation reaction (UOR) is crucial for developing urea‐related energy technologies yet remains a daunting challenge. In this study, a synergistic anomalous hcp phase and heteroatom doping engineering over metallic Ni are found to enhance the UOR. A metal‐organic framework‐mediated approach is proposed to construct Ni nanoparticles (NPs) with designated crystal phase embedded in N‐doped carbon (fcc‐Ni/NC and hcp‐Ni/NC). Significant crystal phase‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…For example, a series of Ni-based nanoparticles encapsulated in N-doped carbon (NC) substrate with different phases, namely fcc-Ni/NC, hcp-Ni/NC, and hcp-MnNi/NC, has been synthesized as catalysts toward the UOR. 1096 It was found that the metallic Ni with unconventional hcp phase was more favorable for catalyzing the UOR with respect to fcc-Ni (Figure 112g). In the meantime, the doping of foreign Mn species further regulated the electronic structure of Ni sites, leading to optimized adsorption/desorption behaviors of crucial reaction intermediates during the UOR process, thereby substantially improving the intrinsic catalytic activity.…”
Section: Catalysismentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a series of Ni-based nanoparticles encapsulated in N-doped carbon (NC) substrate with different phases, namely fcc-Ni/NC, hcp-Ni/NC, and hcp-MnNi/NC, has been synthesized as catalysts toward the UOR. 1096 It was found that the metallic Ni with unconventional hcp phase was more favorable for catalyzing the UOR with respect to fcc-Ni (Figure 112g). In the meantime, the doping of foreign Mn species further regulated the electronic structure of Ni sites, leading to optimized adsorption/desorption behaviors of crucial reaction intermediates during the UOR process, thereby substantially improving the intrinsic catalytic activity.…”
Section: Catalysismentioning
confidence: 99%
“…(i) ECSA-normalized UOR polarization curves of fcc -Ni/NC, hcp -Ni/NC, and hcp -MnNi/NC samples. Reproduced with permission from ref . Copyright 2023 Wiley-VCH.…”
Section: Potential Applications Of Unconventional-phase Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tian et al controlled the crystal structure of Ni metal to prepare metal Ni with an abnormal hcp phase, which is superior to the fcc phase metal Ni reported in many reports. [ 248 ] Therefore, we encourage researchers to regulate the crystal structure of Ni‐based materials to obtain novel materials with better UOR activity. In addition, nano glass (NG) and high‐entropy compounds provide new ideas for regulating the functional properties of catalysts and have good UOR activity.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Among various cost-competitive transition-metal-based materials explored for the OER in freshwater electrolysis, cobalt selenides, possessing varied polymorphs, have drawn huge research attention. In particular, the typical nonstoichiometric cobalt selenide, Co 0.85 Se, has recently aroused intensive interest as a result of its special electronic structure, good corrosion resistance, together with intrinsic half-metallic nature for facile electron transfer, which is in striking contrast with other cobalt selenide polymorphs in semiconducting nature (e.g., CoSe and Co 9 Se 8 ). The above characteristics render Co 0.85 Se to be a promising candidate for expediting seawater oxidation under harsh conditions, whereas further enhancing both catalytic activity and anticorrosion behavior of Co 0.85 Se is a prerequisite to meet strict requirements for selective OER in seawater electrolysis. The aliovalent doping has been well-accepted as a feasible strategy to tailor the intrinsic catalytic capability via regulating surface electronic configuration. Specially, doping of high-valence-state metal species (e.g., Mo, W, Cr, and V) has been demonstrated to be a powerful protocol to modulate the electron density. , Beyond that, interface engineering by integrating different components into one hybrid can not only inherit advantages of each moiety but also afford populated active centers at the interface, and meanwhile, present elevated inherent catalytic ability via the strong interfacial coupling effect. …”
Section: Introductionmentioning
confidence: 99%